Usability study on SPIA v2 for RMN / Sarhan Rozaini Mohamed Radzi - Mohamed Radzi, Sarhan Rozaini (2014)
Sistem Pengurusan Inventori Armada Version 2 (SPIA v2) is an intranet system that was developed for Royal Malaysian Navy (RMN) to facilitate its logistic system. However, the system is not fully used by the RMN personnel due to lack of acceptance and unclear usability issues. Hence, this research project is performed to objectively uncover the system acceptance based on understandability, learnability, operability and attractiveness, to identify usability factors required by users to improve the system design and to propose solution to improve the system design based on the identified usability factors. A survey questionnaire was developed and distributed to 100 users of SPIA v2. Interview was also performed to further understand problems and issues that arise from the use of SPIA v2. Four usability factors from ISO 9126, which are understandability, learnability, operability and attractiveness, is used to designed the questionnaire in evaluating the SPIA v2 system. The result shows that understandability, learnability, operability and attractiveness are the main issues in SPIA v2. A set of proposed solution for future versions of SPIA with some improvements in usability factors are provided at the end of the project. The proposed solution could be used by the system designers to improve SPIA v2, thus enhance acceptance and sustainability of the system.